2011
DOI: 10.1007/s00531-011-0724-5
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic orogenic history of Western Qinling inferred from sedimentation of Tianshui basin, northeastern margin of Tibetan Plateau

Abstract: The Western Qinling orogenic belt marks the northeastern margin of the Tibetan Plateau. Its late Cenozoic orogenic history is recorded in an excellent sedimentary sequence exposed in the Tianshui sub-basin of the Longzhong basin. According to the magnetostratigraphic analysis from the Yaodian and Lamashan sections, we speculate that the late Cenozoic Tianshui basin accumulated lacustrine/floodplain deposits from *14.8 to *2.6 Ma. In addition, detrital apatite fission-track thermochronologic and paleocurrent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Meanwhile, this aridification event is consistent with other mammal fossil and pollen evidence from Qaidam Basin (Chang et al, 2008;Wu et al, 2011). Since the late Pliocene, previous studies have demonstrated that rapid tectonic uplift might have occurred in the northern and northeastern part of the Tibetan Plateau (Li and Fang, 1999;Zheng et al, 2000;An et al, 2001;Fang et al, 2005;Wang et al, 2012a;Li et al, 2014). This uplift may not only disturb the atmospheric circulation pattern and block the penetration of water moisture, promoting the arid climate, but also increase continental weathering (Raymo and Ruddiman, 1992) and influence mammal evolution (Chang et al, 2008;Deng et al, 2011).…”
Section: Climatic Evolution Of Ne Tibetan Plateau and Implications Fosupporting
confidence: 78%
See 2 more Smart Citations
“…Meanwhile, this aridification event is consistent with other mammal fossil and pollen evidence from Qaidam Basin (Chang et al, 2008;Wu et al, 2011). Since the late Pliocene, previous studies have demonstrated that rapid tectonic uplift might have occurred in the northern and northeastern part of the Tibetan Plateau (Li and Fang, 1999;Zheng et al, 2000;An et al, 2001;Fang et al, 2005;Wang et al, 2012a;Li et al, 2014). This uplift may not only disturb the atmospheric circulation pattern and block the penetration of water moisture, promoting the arid climate, but also increase continental weathering (Raymo and Ruddiman, 1992) and influence mammal evolution (Chang et al, 2008;Deng et al, 2011).…”
Section: Climatic Evolution Of Ne Tibetan Plateau and Implications Fosupporting
confidence: 78%
“…Field investigation indicates that sediments of this section are mostly grayegreen mudstones and yellowebrown or reddish-brown mudstones. The detailed lithologic properties and magnetostratigraphic age (>11.1e2.6 Ma) have been reported by Wang et al (2012a). Seventeen new samples were sampled from Lamashan based on differences in sedimentary characteristics, such as lithology, color, and degree of pedogenesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharply increased Caledonian component in the Unit 3 of Wushan1 section and the upper Miocene Yaodian section (Figures j–l) proves that shortening‐related uplift has transmitted from the southern West Qinling to the northern West Qinling and Liupan Shan at the late Miocene (12–10 Ma). Meanwhile, the eastward expansion of deposition from the western Tianshui Basin to the Yaodian‐Lixian region (Figure ) [ Li et al , ; X. X. Wang et al , ] was almost simultaneous with the northeastward progression of topographic growth. We attribute this phase of mountain uplift and basin formation to relocation of crustal shortening from NE‐SW direction to ENE‐WSW direction (Figures a and b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lacustrine and fluvial facies are also present in Yaodian and Lamashan sections, but these sequences were much delayed in contrast with the Wushan and Yawan sequences (Figure ) [ Li et al , ; X. X. Wang et al , ]. It reflects southeastward migration of subsidence from the Wushan Basin to the eastern Tianshui Basin and the Xihe‐Lixian Basin (Figure ) during the late Miocene.…”
Section: Cenozoic Stratigraphy Of Eastern Longzhong Basinmentioning
confidence: 99%